Analisis Pengujian Perangkat Lunak pada Sistem Inventory Gudang Berbasis Web Menggunakan Standar ISO/IEC 29119 - Ananda Ivana Anggraini; Dian Rifan Abdulah; Kukuh Wijarnako; Chairul Anwar (PT Jurnal Cendekia Indonesia, 2025)
This study aims to analyze the software testing results of a web-based Inventory Gudang system using the ISO/IEC 29119 standard. The system tested is an open-source inventory management application utilized to support stock management processes, including master data management, transaction handling, user authentication, and reporting features. The testing process was conducted by applying structured testing activities based on the ISO/IEC 29119 framework, covering test planning, test execution, documentation of test scenarios, and analysis of testing results. The evaluation focused on identifying functional errors, determining their root causes, and assessing their impact on overall system functionality. The testing results indicate that while several core functionalities operate as expected, critical issues were identified in system integration, authentication mechanisms, and routing configurations, which significantly affect system usability and reliability. Based on the analysis, the system is currently not suitable for release without corrective actions. This study provides recommendations for system improvement and emphasizes the importance of applying standardized software testing practices to ensure system quality and operational readiness.